Initial Validity Evidence for the State Mindfulness Scale for Physical Activity With Youth. Issue 4 (2nd October 2017) - Ullrich-French, Sarah; Cox, Anne; Cole, Amy; Rhoades Cooper, Brittany; Gotch, Chad
ABSTRACT: Experiencing mindfulness during movement-based interventions (e.g., yoga) may help support adaptive physical activity motivation processes in youth. However, there is currently no measure for assessing state mindfulness with youth within the context of physical activity. The purpose of this study was to qualitatively and quantitatively evaluate a measure of state mindfulness for physical activity in youth. In study one, cognitive interviews with youth ( N  = 15) ages 8–13 evaluated the State Mindfulness Scale for Physical Activity item comprehension and preference for developmentally worded modifications. Results suggest that problems with item comprehension were more likely in youth younger than 10. In study two, the State Mindfulness Scale for Physical Activity, or a modified version, was administered randomly to middle-school students ( N  = 481). Internal consistency reliability, confirmatory factor analyses, model-based reliability omega, and correlations with theoretically relevant variables combined with the qualitative evidence provided stronger initial support for the use of the original State Mindfulness Scale for Physical Activity with middle-school students.